Disturbance of HSP70 Chaperone Activity Is a Possible Mechanism of Mitochondrial Dysfunction - Belenichev, I. F.; Pavlov, S. V.; Sokolik, E. P.; Бєленічев, Ігор Федорович; Павлов, Сергій Васильович; Соколик, Олена Петрівна (Pleiades Publishing, 2011)
We studied the involvement of HSP70 and Hif1b genes in the development of pathological changes in the brains of experimental animals during ischemia. We found neuro- and mitoprotective characteristics of heat shock protein HSP70 and Hif1b in vitro and under cerebral ischemia due to stabilization of molecules damaged by oxidation, inhibition of nitrosative and oxidative stress and mitoprotective action directed to amelioration of mitochondrial dysfuction. The protective role of these proteins provides a new direction for the development of novel neuroprotective drugs that protect or modulate the genes that encode these proteins.
Keywords: mitochondrial dysfunction; heat shock proteins; chaperones; ischemia